THE EFFECT OF RELIGIOSITY AND TRUST ON INTENTION TO PAY IN ZISWAF COLLECTION THROUGH DIGITAL PAYMENTS - Syafira, Fadillah Nur; Ratnasari, Ririn Tri; Ismail, Shafinar (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
The use of digital payment in Indonesia has increased rapidly. The number of users continues to grow every year, making various zakat institutions, infaq, sadaqah, and waqf start innovating to raise funds using a digital payment system. This excellent innovation seems in contrast with the amount of of zakat funds, infaq, waqf, and alms collected; it is still far below the potential number of funds. Many factors influence the intention to pay of the Muslim community in paying zakat, infaq, endowments, and alms. Some factors that need to be investigated are religiosity and trust factor. The aim of this research is to analysis the religiosity and trust factor towards intention to pay zakat, infaq and endowment. Based on that statement, questionnaires will be given to 200 respondents to determine the effect of these factors on the intention to pay of the Muslim community in paying zakat, infaq, endowments, and alms. Using mix methods between quantitative and qualitative, the data is primary from questioner. The result of this study shows that each religiosity and trust has insignificant and significant related to the intention to pay zakat, infaq, endowments, and alms. However, trust as intervening variable could affect religiosity indirectly, regarding its impact towards intention to pay.Keywords: Digital Payment, Intention to Pay, Religiosity, Trust, ZISWAF